Editorial: Sobukwe, psychology, and politics - Hayes, Grahame; Hook, Derek (PINS-Psychology in Society, 2024)
It is a sign of the times that a journal devoting a special issue to the work and ideas of Robert Mangaliso Sobukwe should feel the necessity to “justify” itself, and especially so a psychology journal. What have Sobukwe’s ideas got to do with psychology, and even a journal of the social in psychology? Previous special issues of PINS (Psychology in society) have usually come about for two reasons: either to highlight some important social phenomenon (like racism, HIV/AIDS), or to bring attention to some neglected area of investigation (like social cohesion). The work and ideas of Robert Sobukwe have certainly suffered from intellectual neglect, not to mention the marginalization of Africanist thought through the hegemony of the Charterist political project. Mcebisi Ndletyana (2013) has made this point forcefully. He notes that repeated opportunities to commemorate Sobukwe’s legacy were met with a telling silence: “This silence tells us, in its own unique way, of an official quest to forget Sobukwe … Attempts to erase Sobukwe’s memory in our public consciousness are indicative of how those in power legitimise themselves.” (Ndletyana, 2013: 15).